SINERGI STRATEGI CUSTOMER BONDING UNTUK MEMPERTAHANKAN LOYALITAS PELANGGAN DI PIZZA HUT DELIVERY KOTA KEDIRI - Laksono, Bayu; Aliami, Sri; Soeprajitno, Edy Djoko (Universitas Nusantara PGRI Kediri, 2022)
The study aims to determine the synergy of Customer Bonding strategies to maintain the loyalty of PHD Kediri customers. The research approach used is qualitative with the case study method. Data collection by interview and observation. Data validation using data source trianggulation. The results showed that the Customer Bonding strategy consists of five indicators that can maintain customer loyalty. (1) Awarenes bonding using advertising, direct marketing and interactive marketing. (2 Identity Bonding is in the form of green marketing and involving the community. (3) Relationship Bonding in the form of public relations, sales promotion, and personal selling, (4) Community Bonding in the form of event sponsorship and club organizers. (5) Advocacy Bonding with new product expose, commitment and . word of mouth. The success of PHD Kediri in carrying out the Customer Bonding Strategy is in terms of increasing the frequency of repurchases based on member identities.